1979
DOI: 10.2337/diab.28.12.1102
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Selection for Diabetogenic Traits in Yucatan Miniature Swine

Abstract: Yucatan miniature pigs have been selectively bred for reduced and increased glucose clearance during an intravenous glucose tolerance test. Pigs with low glucose clearance rates (low K) have been selected through the F-5 generation. They have a significantly reduced rate of glucose clearance and a blunted peripheral IRI increase in response to the challenge. Through the F-5 generation, heritability of glucose tolerance is estimated at 0.26. Sporadic fasting blood glucoses in excess of 100 mg/dl are seen in lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…63 (2) Metabolism of foodstuffs, 63 specifically lipoprotein metabolism (References 24, 25, and 51 and the present report), is similar to that in humans. (3) Swine have a propensity toward sedentary habits and obesity; unlike dogs, which will pace in their cages if not adequately exercised, pigs are content to be sedentary.…”
Section: Need For a Suitable Animal Model: Advantages Of The Porcine supporting
confidence: 67%
“…63 (2) Metabolism of foodstuffs, 63 specifically lipoprotein metabolism (References 24, 25, and 51 and the present report), is similar to that in humans. (3) Swine have a propensity toward sedentary habits and obesity; unlike dogs, which will pace in their cages if not adequately exercised, pigs are content to be sedentary.…”
Section: Need For a Suitable Animal Model: Advantages Of The Porcine supporting
confidence: 67%
“…Attempts to genetically select a strain of diabetic pigs have been made (38,39,40) but have, so far, not been confirmed to be successful (19). The use of pancreatectomized animals as a model of diabetes (15,33,34,50) has the disadvantage of also removing the exocrine function of the pancreas and the non-␤-cell endocrine cells of the islets of Langerhans, and although performance of partial pancreatectomy might be useful for induction of mild diabetes, this method clearly is more invasive compared with the administration of STZ.…”
Section: Discussionmentioning
confidence: 99%
“…Of special interest for the study of diabetes is the similarities to humans found in the clinical chemistry (7,10,12,14,24,26,55), nutrition and gastrointestinal tract (4,8,11,20,35,40,51), pancreas development and morphology (21,36,37,44,49,54), and metabolism (3, 35). These characteristics make swine an interesting species for studies of metabolic abnormalities in diabetes.…”
mentioning
confidence: 99%
“…Large animals with spontaneous diabetes include the monkeys (Macaca nigra, Saimiri sciureus, squirrel monkey, Macaca mulatta, and occasional others 9 ), dogs, [golden retrievers (G. A. Padgett, personal communication) and Keeshonds 10 ], Yucatan miniature pigs, 11 and certain rabbits. 12 this symposium).…”
Section: Availabilitymentioning
confidence: 99%